Sedimentary analysis of soil samples (Scottish Historical and Archaeological Internet Reports, 2005)
The acidic nature and relatively low organic and moisture content of the site has precluded the preservation of bone, shell, uncarbonized plant macrofossils and insect remains. The routine soil tests confirmed the presence of an altered relic soil beneath the cairn. The correlation between the enhance magnetic signal and the high concentration of carbonized plant macrofossils in the ash spreads confirms the taphonomy of the archaeobotanical assemblage from the burning and dumping of ash from peaty turves and other incorporated plant material into the main body of the cairn. Two of the three fills within the cists displayed magnetic enhancement from the input of ashy material from the ash spreads. Therefore the ash spreads were incorporated into the body of the cairn immediately after the cist was constructed or the cist was not lidded when the deposit was made. The excavation demonstrated that the ash layer was probably cut to insert the cist. It is likely that the ash was redeposited in the cist during this process.